2009
DOI: 10.7202/000379ar
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of hydrocarbon-contaminated soils with emphasis on the effect of petroleum hydrocarbons on the growth of plant species

Abstract: To date, many developing countries such as Iran have almost completely abandoned the idea of decontaminating oil-polluted soils due to the high costs of conventional (physical/chemical) soil remediation methods. Phytoremediation is an emerging green technology that can become a promising solution to the problem of decontaminating hydrocarbon-polluted soils. Screening the capacity of native tolerant plant species to grow on aged, petroleum hydrocarbon-contaminated soils is a key factor for successful phytoremed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 28 publications
4
32
0
3
Order By: Relevance
“…The uniformity in germination of A. hypogaea and S. bicolor may imply that both plants have equal tendencies to resist the effect of crude oil. This may be a reason for their existence in the wild in oil contaminated fields of Iran (Shirdam et al, 2008). The progressive decrease in the germination of both plants as crude oil contamination increased corresponds with the reports of earlier studies by Merkl et al (2004b), Njoku (2008) and Oyedeji (2012).…”
Section: Resultssupporting
confidence: 86%
“…The uniformity in germination of A. hypogaea and S. bicolor may imply that both plants have equal tendencies to resist the effect of crude oil. This may be a reason for their existence in the wild in oil contaminated fields of Iran (Shirdam et al, 2008). The progressive decrease in the germination of both plants as crude oil contamination increased corresponds with the reports of earlier studies by Merkl et al (2004b), Njoku (2008) and Oyedeji (2012).…”
Section: Resultssupporting
confidence: 86%
“…However, plants exhibited lower growth rates here than in any other site. This is in accordance with results in Merkl et al (2005) and Shirdam et al (2008); these authors also found impaired growth in plants that grew on petroleum contaminated soils in tropical coastal areas. Excess humidity in the presence of hydrocarbons seemed to be the main cause of death in the CSTUs; this humidity was probably due to not only the clay-like texture of the soil, but also to the surface migration of hydrocarbons, which may have caused leaf necrosis, a reduction in photosynthesis, and a reduction of aboveground and belowground biomass in plants from our experiment, as reported in other extraction sites (Adam and Duncan, 2002).…”
Section: Species Performancesupporting
confidence: 92%
“…At a global level, some studies have been carried out to select plant species for soils disturbed by petroleum extraction activities, and to assess the effects of these species on soil characteristics in tropical and subtropical ecosystems (e.g., McConkey et al, 2012 andWillis et al, 2005 in America and Mohsenzadeh et al, 2010;Shirdam et al, 2008 andXia, 2004 in Asia). However, as far as we know there are no such studies in the Amazon Basin.…”
Section: Introductionmentioning
confidence: 99%
“…These plants were chosen because they grow in a wide range of soil conditions and can withstand high saline-alkali stress, which is common in oil fields in many parts of China. Hydrocarbon contamination is known to significantly reduce the growth of the plants, and the corresponding TPH degradation efficiency of the different plant species is reported to differ widely (Shirdam et al, 2008;Euliss et al, 2008). The TPH degradation rate among various plant species depends on the microbial population in the rhizosphere of these plants.…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic reaction of the plants and microorganisms, rhizoremediation showed a higher degradation rate of petroleum pollutants than microbial remediation and phytoremediation (Gurska et al, 2009;Xin et al, 2008;Escalante-Espinosa et al, 2005). Several plant species, including ryegrass, sorghum, maize, alfalfa, Bermuda grass, rice, legume, sorghum and beggar ticks, are effective in degrading total petroleum hydrocarbons (TPH) (Nedunuri et al, 2000;Kaimi et al, 2007;Merkl et al, 2005;Shirdam et al, 2008). The TPH content is an important factor of rhizoremediation and influences the bioremediation process.…”
Section: Introductionmentioning
confidence: 99%